Hungarian Monitoring, 29 January 1988 . [Magyar rádiófigyelő], 1988. január 29 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Helsinki Accords International Association talks in Moscow - GDR-FRG relations after events in Berlin - GDR-Czech relations after Kohl's visit - Bulgarian CP's national assembly - Mubarak in Washington - French-British summit Domestic Affairs: - 30% drop in size of Young Communist League (KISZ) - Report on the future use of the Gabčíkovo-Nagymaros dam - Foreign adverts can be broadcast on Hungarian radio and television Economy: - Miklós Németh at Alliance of Technical and Natural Sciences Societies (METESZ) on the economic situation, tasks - Central Statistical Office (KSH) report on the previous year - More opportunities for personal investment: on Kft. limited liability companies Külpolitika: - Helsinki Tárgyalások Nemzetközi Szövetségének moszkvai tárgyalásai - NDK és NSZK viszonya a berlini események után - NSZK-cseh kapcsolatok Kohl látogatása kapcsán - A Bolgár KP országos értekezlete - Mubarak Washingtonban - Francia-brit csúcstalálkozó Belpolitika: - 30 százalékkal csökkentik a KISZ apparátusát - Riport összeállítás a bős - Nagymarosi vízlépcső majdani hasznosításáról - Külföldi reklámokat is sugározhat a magyar rádió és tv Gazdaság: - Németh Miklós a METESZ-ben a gazdaság helyzetéről, feladatairól - KSH jelentése a tavalyi évről - Bővülnek a lehetőségek a magánpénzek befektetésére: a KFT-kről